2018
DOI: 10.1111/jch.13159
|View full text |Cite
|
Sign up to set email alerts
|

Failure to confirm high blood pressures in pediatric care—quantifying the risks of misclassification

Abstract: Pediatric practice guidelines call for repeating an elevated office blood pressure (BP) at the same visit, but there are few data available to support this recommendation. We compared the visit results in children aged 3 to 17 years with a BP reading ≥95th percentile (n = 186 732) based on the initial BP and the mean of two BP readings, using electronic medical records from 2012-2015. Failure to repeat an initial BP reading ≥95th percentile would lead to a false "hypertensive" visit result in 54.1% of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…18 only, which would lead to unnecessary follow-up. 7 In the present study, we found that the mean value of the last two readings when three BP readings were recorded at a single visit was better than any individual reading to identify those children and adolescents with hypertension. Consistent with our findings, a previous study showed that BP decreases greatly between the first two measurements but less so between the second and third measurements at a visit.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…18 only, which would lead to unnecessary follow-up. 7 In the present study, we found that the mean value of the last two readings when three BP readings were recorded at a single visit was better than any individual reading to identify those children and adolescents with hypertension. Consistent with our findings, a previous study showed that BP decreases greatly between the first two measurements but less so between the second and third measurements at a visit.…”
Section: Discussionmentioning
confidence: 47%
“…One major challenge is how to best balance the increased rate of false positives using limited BP mesurements. 7,8 Among adults, single BP measurement at a visit might not be enough to define hypertension, 17 especially for people with a higher initial BP reading. 18 only, which would lead to unnecessary follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…8 BP measurement in children can be neither accurate nor precise, with data suggesting that substantial misclassification can result from reliance on single values. 21 That we did not identify clear differences in BP percentile patterns may not be surprising given these issues. Further study is necessary to determine whether tracking SBP percentiles could help identify critical periods when racial differences emerge.…”
Section: Discussionmentioning
confidence: 74%
“…Diagnosis of HTN is further dependent upon taking multiple BP readings, whose interval of repetitive measurements is dependent upon the initial readings themselves. About 48.2% of stage I HTN diagnoses are correct, and only 35.0% of stage II HTN diagnoses are correct [39]. Thus, follow-up appointments must be carefully coordinated to assure accuracy.…”
Section: Pediatric Htn Is Underdiagnosed With Incomplete Managementmentioning
confidence: 99%